Numerical Simulation of Wave–Current Force Characteristics of Horizontal Floating Cylinder in Heave Motion - Xiaoguo Zhou; Qingdian Jiang; Yan Wang; Linfeng Chen; Shuqi Wang; Kunpeng Wang (Journal of Marine Science and Engineering, 2022)
This paper presents the characteristics of the heave motion responses and hydrodynamic forces of a horizontal floating circular cylinder during a wave–current interaction. A two-dimensional numerical model based on the CFD (Computational Fluid Dynamics) method for modeling wave flow is validated and verified. The hydrodynamic characteristics of the horizontal floating cylinder during heave motion were calculated and analyzed under the conditions of different k values (stiffness of spring), wave amplitudes, submerged depths, and flow rates. The results show that, with the increase in the k value, the vibration amplitude of the cylinder first increases and then decreases. The vibration amplitude peak is achieved, the vibration frequency is consistent with the wave frequency, and a resonant motion takes place. When the wave amplitude and flow rate are fixed, the maximum vibration amplitude decreases as the wave period increases. When the cylinder is half-submerged, the effect of the current on motion is significant; the vibration amplitude is less than the wave amplitude. When a quarter is submerged, the vibration amplitude is larger than that of the half-submerged cylinder at each k. The maximum amplitude is greater than the wave amplitude, and the vibration amplitude reaches the minimum at the moderate flow rate for each k.